Microcirculatory bed in former smokers with arterial hypertension - N. V. Korneeva; B. Z. Sirotin (Лечащий Врач)
The cessation of smoking in terms of the effectiveness of primary and secondary prevention of cardiovascular events is comparable with drug therapy and invasive interventions. Comprehensive assessment of the state of the microcirculatory bed in former smokers with arterial hypertension was performed.